PELATIHAN GRAPHIC DESIGN SEBAGAI UPAYA MENINGKATKAN KREATIVITAS ORGANISASI MAHASISWA UNIVERSITAS 'AISYIYAH SURAKARTA - Ernawati, Fajriya; Dawis, Aisyah Mutia (Jurnal Pengabdian Pada Masyarakat Indonesia, 2022)
In the current digital and millennial era, the development of the design world is progressing very rapidly. The role of graphic design in all business fields is needed. This can be proven by the many business fields that utilize the expertise of graphic designers. The Student Organization (ORMAWA) is a forum for students to develop their own capacity in the form of positive ideas, appreciation, initiation, creativity and also to accommodate the talents, interests and potentials possessed by students in various relevant activities. In various NGO activities, there are still many ormawa administrators who do not understand graphic design, especially in terms of using graphic design software, namely Photoshop. So that the making of posters, leaflets, brochures, banners and activity banners must be designed with instant templates. Therefore, this training activity was held to provide knowledge to ormawa about the use of graphics processing software for activities that require graphic and photo processing.